A social realist view of contextual disruption through (un)conferencing - de Klerk, Danie; Frade, Nelia; Ramrung, Arthi; Fontaine-Rainen, Danielle (Critical Studies in Teaching and Learning, 2024)
Disruptions within higher education are seldom effortless and often provocative. They may result in a break from traditional, established educational models of knowledge transmission, offering alternative ways of accessing and cocreating knowledge. In 2021, the Higher Education Learning and Teaching Association of Southern Africa (HELTASA) adopted an (un)conferencing methodology for its annual conference. In this paper, the association’s Student Learning Project Team explores contextual disruption against the (un)conferencing backdrop. Critical reflective accounts by project-team members provide the empirical grounding for the paper. First, the notions of context and contextual disruption are discussed. Second, the reflective accounts are analysed using Archer’s structure, culture, and agency, as analytical framework. Third, Archer’s morphogenetic framework is used to appraise whether change or stasis occurred within the project team. Finally, recommendations for others wishing to facilitate intentional contextual disruption are shared. Ultimately, the article provides insight into the intricacies of contextual disruption as part of (un)conferencing.